Targeting interleukin-13 in idiopathic pulmonary fibrosis: from promising path to dead end. Issue 6 (13th December 2018) - Wijsenbeek, Marlies S.; Kool, Mirjam; Cottin, Vincent
The pathogenesis of idiopathic pulmonary fibrosis (IPF) is characterised by repeated subclinical injury to the alveolar epithelium, leading to injured alveoli, myofibroblast recruitment and activation, resulting in aberrant wound healing with uncontrolled matrix deposition and progressive fibrosis. However, inflammation and immunity are also thought to play a modulatory role in IPF pathogenesis. Data from IPF patients and experimental animal models have shown that type 2 inflammatory processes are activated in pulmonary fibrosis [1, 2]. The main type 2 cytokines are interleukin (IL)-13 and IL-4, produced by T helper 2 (Th2) cells and type 2 innate lymphocytes; both are suggested to play a prominent role in fibrosis development [1, 2]. As type 2 immunity is central in the immunopathology of allergic asthma, compounds targeting IL-13 and IL-4 have been developed for asthma [3–6]. Targeting IL-4/IL-13 with SAR156597 failed to demonstrate an effect on lung function decline for patients with idiopathic pulmonary fibrosis; these results are in line with the negative results of two other trials targeting IL-13 in this disease http://ow.ly/J0HF30mAB3J